Sensitivity and Specificity of a Weight Distribution Platform for the Detection of Objective Lameness and Orthopaedic Disease - Clough, William T.; Canapp, Sherman O., Jr.; Taboada, Luis De; Dycus, David L.; Leasure, Christopher S. (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Introduction Weight distribution and off-loading at the stance are commonly used subjective assessments during the orthopaedic examination. The clinical relevance, sensitivity and specificity of limb off-loading have not yet been established. The aim of the study was to assess off-loading on a weight distribution platform (WDP) and determine the sensitivity and specificity at various cut-off points for the detection of objective lameness (OL) and orthopaedic disease (OD).Materials and Methods The total pressure index was used to determine OL on a pressure-sensitive walkway (PSW). Normal weight distribution on both the PSW and WDP was considered 30/30/20/20. A total pressure index standard deviation of 2 was used. The sensitivity and specificity of the WDP for the identification of OL and OD was determined at cut-off points 1 to 6 below normal weight distribution values.Results All patients in the study (n = 50) had confirmed OD. The PSW identified 36/50 (74%) patients as OL; these were deemed to be OL for sensitivity and specificity analysis of WDP data. At cut-off point 1, the WDP had the highest sensitivity for OD (84%) and OL (97%). At cut-off point 6, the WDP had the highest specificity for OD (98%) and OL (98%). The highest combination of sensitivity and specificity for both OD (1.65) and OL (1.80) was at cut-off point 2.Discussion/Conclusion The WDP provided the highest combined sensitivity and specificity at cut-off point 2 below the normal value for the detection of both OL and OD.
Keywords: weight distribution platform; lameness evaluation; objective assessment; stance evaluation